Harvard business review on corporate strategy (Harvard business review on corporate strategy BostonUS, 1999)
Discusses the role of resources, administrative organization, and businesses, in the formulation of great corporate strategies. Explains why some competitors are more profitable than others; how to practise core competence; and how to develop sensible diversification strategies. Warns against the hasty pursuit of synergy, and addresses changes which multi-national companies need, in order to compete successfully in the present post-imperialist era. Also discusses the strategic significance of building and managing a company's capabilities.
Located in the Learning Resource Centre.